Effects of grazing management and levels of concentrate supplementation on parasite establishment in two genotypes of lambs infected with Haemonchus contortus - Simon P Ginting; K.R Pond; Subandriyo . (Indonesian Center for Animal Research and Development (ICARD), 1996)
The effects of grazing systems, levels of feed supplementation and genotypes of sheep on the establishment ofHaemonchus contortus were studied in 36 St . Croix x Sumatra crosses (HC) and 36 Sumatra (S) male lambs . The lambs were artificially infected with Haemonchus larvae (L3) at a rate of 3,000 L3 per animal and fed concentrate supplement at 0 .5% body weight (BW) or at 1 .6% BW. The animals grazed clean Brachiaria brizantha pastures . Lambs grazing GM1 (grazing system with a 6-week rotational cycle) had egg counts of 3,936 t 1 .525 at week 18, and 29% of the lambs had PCV ranging from 7 .8 to 14 .6% . Lambs in GM3 (grazing system with a 12-week grazing cycle) had egg counts of 6,714 t 2,075 at week 28, and 24%ofthe lambs had PCV ranging from 7 .9 to 13.3% At these periods, all lambs in both GMI and GM3 were dosed with anthelmintics to prevent the death of the animals . Although the overall mean egg counts (4,543 t 318) of lambs on GM2 (grazing system with a 1-week grazing and 6-week resting periods) were higher (P<0 .001) than on GMI (2,944 t 325) or on GM3 (2,159 t 418), it was achieved without dosing with anthelmintics, since only I 1%ofthe Iambs in GM2ever reached PCV values less than 15%. Lambs fed supplements at 1.6%BW had lower (P<0.001) egg counts and higher (P<0 .001) PCV and serum protein than lambson 0.5 %BW supplement group . Egg counts and PCV values were not different (P>0 .10) between HC and the S lambs when fed supplement at 0.5% BW, but on 1 .6% supplement BW group, the egg counts were lower (P<0.001) in HC. It is concluded that a one-week grazing and a six- week resting system was superior than grazing systems with a 6- or 12-week rotational cycle . Improving the nutritional status of lambs by increasing the level of supplement offered could depress the establishment of Haemonchus in the Iambs . The HC and S lambs showed similar response to supplements at 0 .5% BW, but at 1 .6% BW the HC responded better than the S. Key words: Grazing management, Haemonchus contortus, feed supplement, sheep